In vivo assignment of methylmalonic acid in breast tissue using 2D MRS and relationship with breast density, menopausal status and cancer risk. (2nd November 2022) - Santamaría, Gorane; Naude, Natali; Bennett, Ian; Vosburgh, Kirby; Ganau, Sergi; Bargalló, Xavier; Malycha, Peter; Mountford, Carolyn
Abstract : Background: Methylmalonic acid (MMA) is linked to progression and aggressiveness of tumours. A recent study showed that high levels of circulatory MMA directed genetic programs promoting cancer progression. Purpose: To evaluate in vivo two‐dimensional correlated spectroscopy (2D COSY) data from women at elevated risk of breast cancer to determine if resonances consistent with MMA are present, and if so to correlate levels with breast density, menopausal status and risk categories. Materials and methods: With institutional review board approval, 106 women at elevated risk (mean age 47), including 46 participants at medium risk, 43 at high risk with no known mutation and 17 BRCA‐ mutation carriers, were recruited. Breast density was assessed using a T 2 sequence. A T 1 sequence was used to place the voxel for the 2D COSY data. Peak volumes were normalized to the methylene peak at (1.30, 1.30) ppm. Chi‐squared and Mann–Whitney tests were used. Results: Two resonances are assigned on the diagonal at 3.15 ppm and 3.19 ppm consistent with and denoted MMA1 and MMA2 respectively. MMA1 and MMA2 increased in parallel with increased risk. BRCA ‐mutation carriers recorded an increase in mean MMA1 of 120% ( p = 0.033) and MMA2 of 127% ( p = 0.020) in comparison with participants with no known mutation. BRCA ‐mutation carriers with dense breasts recorded a significant increase in mean MMA1 of 137% ( p = 0.002) and in mean MMA2 of 143% ( p = 0.004) compared with BRCA ‐mutation participants with low‐density breast tissue. MMA1 and MMA2 were higher in premenopausal women with dense breasts compared with those with low‐density tissue. The highest values of MMA were recorded in BRCA ‐mutation carriers. Conclusion: Two tentative assignments are made for MMA in breast tissue of women at elevated risk for cancer. BRCA ‐mutation carriers exhibited higher values of MMA than those with no known mutation. Premenopausal women with BRCA mutation and dense breasts recorded the highest levels of MMA compared with other categories. Abstract : Methylmalonic acid is linked to tumour progression. Here we assign methylmalonic acid in breast tissue of women with increased cancer risk, using in vivo 2D COSY in a 3 T clinical scanner. Relationships of this molecule with breast density and menopausal status might provide insight into its role in tumour development.